Prevention preferable to treatment: 3 case reports of patients experiencing right-sided heart failure after Ebstein anomaly correction. Issue 1 (January 2017) - Luo, Ming; Lin, Jing; Qin, Zhen; Du, Lei
Abstract: Rationale: Ebstein anomaly is a common congenital heart disease that may induce severe tricuspid regurgitation and dilation of the "atrialized" portion of the right ventricle. Patients who undergo surgery to correct Ebstein anomaly are at high risk of postoperative right-sided heart failure, yet little is known about what pre-, peri-, or postoperative procedures may help reduce this risk. Patient concerns: Here, we describe 3 cases of adults with Ebstein anomaly who underwent corrective surgery and in whom right-sided heart failure occurred with severe tricuspid regurgitation detected by transesophageal echocardiography. Diagnoses: Ebstein anomaly. Intervention: Various approaches were applied to prevent right heart failure: perioperative control of atrial and ventricle arrhythmia, protection of myocardium, reduction of right-side cardiac workload after cardiopulmonary bypass, and mechanical support for right heart. Outcomes: One of the 3 patients died, another experienced kidney failure despite postoperative support on extracorporeal membrane oxygenation, and the third patient survived without complications. Lessons: Our case series suggests that surgical prognosis can be improved through aggressive preoperative treatment, vasoactive and anti-arrhythmia medications, and comprehensive measures designed to reduce myocardial injury, prevent myocardial edema, and reduce pre- and afterload on the right ventricle.